On the improvement of the single-site lightning distance estimation by using the time-delay correction - Zhou, Jiahao; Zhang, Qilin; Song, Lin; Zhang, Junchao; Dai, Bingzhe; Li, Jie; Yang, Jing; Wang, Yao; Gu, Jiaying; Zeng, Jinquan (Frontiers in Earth Science, 2023)
Due to the propagation effect, the arrival time of ground wave peak is delayed when sferics propagate at long distances. In this paper, we propose a new method combined with an analytical algorithm to correct the effect of the ground wave peak time delay and calculate the ionosphere height using the difference between the arrival time of the ground wave and the skywave. The results show that, with an extra increase of the propagation distance by 100 km, the delay in arrival time of the ground wave peak is increased by 0.9 μs on average. For the first reflectance height and the second reflectance height, the maximum heights observed at night are 86 km and 89 km, and the minimum heights during the day are 66 km and 69 km, respectively. Using the difference in arrival time between the ground wave and skywave, and the ionosphere equivalent reflection height, a single-site is used to estimate the distance of lightning occurring within 900 km, and the method has an average relative error of 14.6%, the average absolute error of 128.8 km and the median distance error is 52.6km, the percentage of data with estimated deviation within 10% increased from 52% to 65%.